ECONOMIC ANALYSIS OF TOMATO MARKETING IN ILORIN METROPOLIS, KWARA STATE, NIGERIA - Salau, Shehu Abdulganiyu (Journal of Agricultural Sciences (Belgrade), 2017)
Marketing of tomatoe is a complex phenomenon due to their perishable nature, seasonality and bulkiness, and as such, tomatoe production requires an efficient marketing system. Studies on tomatoe marketing in the study area are rare in the literature. Thus, this study analyzed tomato marketing in Kwara State, Nigeria. Simple random sampling technique was used in the selection of one hundred and twenty tomato marketers in the study area. A well-structured questionnaire was used for data collection. Data collected were analyzed using descriptive, Herfindahl Index, costs and returns and multiple regression analysis. and inferential statistics. The study revealed that most (70%) of the marketers were female with mean age of 39.5 years. The Herfindahl Index of 0.008 revealed that tomato market tends toward pure competition. Furthermore, the costs and returns analysis indicated that tomato marketing is a profitable venture in the study area with a monthly gross margin of N328,095. Furthermore, the regression analysis indicated that about 96% of the total variation in net returns was explained by the independent variables. Moreover, the study revealed that purchase cost, labour cost, transport cost and marketing experience are important in determining the net returns of tomatoes marketers. Most (30%) of the respondent identified finance to be their major constraint. This study therefore recommends that tomato marketers should pool their resources together and form cooperative groups for them to reap the benefits of economics of scale. Also, policies and strategies that lower the costs of marketing should be vigorously pursued.